JUDICIAL PROFESSION ETHICS IN JUDICIAL INDEPENDENCE AND RESPONSIBILITY - Fauzan (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Being a judge is not an ordinary profession. Judge is a title representing untouchable, free-ofgossips, smart, and noble persons who do not have bad track-records. And for this reason, they are titled Your Honor. The judge has the most vital position in judicature. It is on them all parties, both defendants and plaintiffs, put all their respects and hopes in courts. The fate of one’s belongings, rights, obligations, credibility, and even one’s life, is in the hands of a judge.